Metode Peningkatan Kecerdasan Spiritual Perspektif Mahasiswa STIBA Ar Raayah Sukabumi - Abdul Halim Muhammad; Kristiana; Nidaul Jannah (Jurnal Dirosah Islamiyah, 2025)
In this modern era, many people often feel spiritual aridity due to the loss of meaning of life in the midst of material and technological advances. Focusing on material attainment and the busyness of life makes the connection with the spiritual aspect diminished which triggers a sense of inner emptiness. This study aims to analyze and explain methods in improving the spiritual intelligence of STIBA Ar Raayah Sukabumi students' perspectives by applying qualitative approaches and descriptive methods. Data were collected using questionnaire techniques and in-depth interviews. The results of the study show that several methods applied in increasing spiritual intelligence according to STIBA Ar Raayah Sukabumi students include; istiqamah in prayer, dhikr to remember Allah, take time to meditate, isolate yourself (Uzlah) to focus on worship, and Tazkiyah al Nafs to purify the soul. By applying this method, students can deepen their spiritual relationship with God and improve their quality in a sustainable manner.